THE INFLUENCE OF FINANCIAL SELF-EFFICACY ON STUDENTS' INVESTMENT INTEREST WITH INVESTMENT KNOWLEDGE AS A MODERATING VARIABLE - Sari Mujiani (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Investment is the most appropriate way to increase money for students who are busy with various activities. There are several factors that can influence students' investment interest, including Financial Self Efficacy and knowledge of investment itself. Therefore, this research aims to analyze the influence of Financial Self Efficacy on Students' Investment Interest with Investment Knowledge as a moderating variable which researchers believe can strengthen the influence of this variable. This research is a quantitative research with an explantory approach. The data used in this research is secondary data distributed through a questionnaire scale containing 20 question items to 250 students of Asy-Syafi'iyah Islamic University with the criteria of 3 months of investing across all platforms with consideration of investment consistency and adjusted to the average student investment. The data collected in this study was analyzed using PLS 3.0. The research results show that the Financial Self Efficacy variable has a positive relationship and a significant influence on the Student Investment Interest variable because increasing self-confidence in managing finances will increase the financial potential of Asy-Syafi'iyah students to become more prosperous and ultimately students will manage their finances. his finances are as good as possible. One way is by investing. Apart from that, the Investment Knowledge variable can moderate the influence of the Financial Self Efficacy variable on the Student Investment Interest variable because increasing investment knowledge in students will make their self-confidence higher. In the end, student savings increase and students continue to think about expanding them. One way is by investing. Keywords : Financial Self Eficacy, Investment Interest, Investment Knowledge